A validation study on knowledge sharing, collaborative culture, beneficiary participation, on the nonprofit effectiveness of Malaysian nonprofit organizations / Nurul Hidayana Mohd Noor, Siti Hajar Abu Bakar Ah and Mohd Awang Idris - Mohd Noor, Nurul Hidayana; Abu Bakar Ah, Siti Hajar; Idris, Mohd Awang (Universiti Teknologi MARA, Shah Alam, 2017)
The objective of this study is to validate and explain previous empirical research findings on the influence of three important component of intellectual capital (IC) that are knowledge sharing, collaborative culture, and beneficiary participation on the effectiveness of Malaysian nonprofit organizations. Using a semi-structured interview, this study aims to explain these outcomes as well as to verify the empirical model. This study begins by extracting data collected from six key informants and data were analyzed using a combination of deductive and inductive approach. The findings were presented based on the identified and derived themes. Based on a survey response from 271 participants, knowledge sharing and beneficiary participation have a positive influence on both external and internal effectiveness, except for collaborative culture. The findings confirmed the empirical model and provide some explanation on the insignificant effect of collaborative culture. In addition, among the major finding is the identification of leadership as enabler in fostering the relationships between knowledge sharing, collaborative culture, beneficiary participation, on nonprofit effectiveness.